Her scandalous pursuit eaudiobook - Camp, Candace (The Mad Morelands, 2020)
Thisbe Moreland is used to men not taking her seriously. As a scientist, she's accustomed to being the only woman at lectures and meetings, her presence met with scorn and derision. So it comes as a pleasant surprise when she sits next to a handsome young man who is actually interested in having a conversation about science. Desmond Harrison cannot believe his good fortune when he sits next to Thisbe—she's intelligent and incredibly beautiful. He longs to see her again—but he's ashamed of his low birth. Not to mention his employment with the infamous Professor Gordon, a formerly respected scientist who turned to spiritualism and is now deeply scorned. When Professor Gordon demands that Desmond recover an artifact for him—an ancient object reputed to have terrible power, known as the Eye of Annie Blue—Desmond realizes that only Thisbe holds the key. Desmond must choose between his love for Thisbe and his loyalty to his mentor . . . but humanity's very future will depend on his choice. Contains mature themes.